1991
DOI: 10.1111/j.1744-7976.1991.tb03589.x
|View full text |Cite
|
Sign up to set email alerts
|

Testing for Asymmetric Pricing in the Alberta Pork Market

Abstract: Asymmetry tests have been used by agricultural economists to determine if the effects of price changes in one region or level in the marketing channel are transmitted to other regions or levels in the marketing channel in an identical manner for price increases and decreases. Two tests are normally conducted: sum of coefficients tests and speed of adjustment tests. In this analysis, these two tests are conducted on weekly price response equations that relate Alberta and Ontario price changes. Six separate peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…At a micro perspective, Kinnucan and Forker (1987), Hahn (1990), Bernard and Willett (1996), and Capps and Sherwell (2007) found that price transmission elasticities in conjunction with rising farm prices generally are larger than corresponding elasticities associated with falling farm prices. On the other hand, Ward (1982) and Punyawadee et al (1991) argued that it should be another way round.…”
Section: Methodsmentioning
confidence: 99%
“…At a micro perspective, Kinnucan and Forker (1987), Hahn (1990), Bernard and Willett (1996), and Capps and Sherwell (2007) found that price transmission elasticities in conjunction with rising farm prices generally are larger than corresponding elasticities associated with falling farm prices. On the other hand, Ward (1982) and Punyawadee et al (1991) argued that it should be another way round.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, Punyawadee et al (1991) propose a model for spatial asymmetry applied to Canadian data. This paper investigates whether the price of pork in Ontario has an asymmetric impact on the correspondent price in Alberta, over the period January 1965–December 1989.…”
Section: Early Asymmetric Modelsmentioning
confidence: 99%
“…There is an extensive list of studies that have used the above techniques. Examples include studies on asymmetry in farm-to-retail price transmission in the dairy sector (Kinnucan and Forker, 1987), price asymmetry in the U.S. pork markets (Boyd and Brorsen, 1988), asymmetry in spatial fed cattle markets (Bailey and Brorsen, 1989), price transmission asymmetry in pork and beef markets (Hahn, 1990), a study of the Alberta pork market (Punyawadee, et al 1991), price asymmetry in the international wheat market (Mohanty, et al, 1995), price asymmetry in the peanut butter market (Zhang, et al, 1995), asymmetric price relationships in the U.S. broiler industry (Bernard and Willett, 1996), asymmetries in farm to retail price transmission of fresh tomatoes, onions, powder milk, soluble coffee, rice, and beans in Brazil (Aguiar and Santana, 2002), and price asymmetry of fresh tomatoes in the U.S. (Girapunthong et al, 2003).…”
Section: Price Transmission Estimation Methodsmentioning
confidence: 99%